Duffy, Medieval Dublin X (Holm) - HOLM, POUL (My University, 2011)
Ten years, ten volumes. Medieval Dublin arrives like clockwork. The series has brought to light an exact number of 100 papers on the city and its hinterland. Contributions have been almost equally drawn from archaeology and history, including art history and literature. In all we now have more than 3,000 pages of academic research into the history of medieval Dublin. It is an impressive accumulation of scholarship in such a short time and no other city in Ireland and indeed few in Europe can count themselves so lucky. Medieval urban history is being well served by its Friends of Medieval Dublin, an academic community of diverse and committed talent. This year?s publication, volume X , is a high mark of the series. It opens with a moving tribute to Simon Dick, archaeologist and Friend of Medieval Dublin who left a legacy of investigations that will inform our understanding of the city in the future. The volume ends with a hitherto unpublished survey of the medieval Irish town by the late A J Otway-Ruthven. Her survey from 1975 is of historiographical interest if it has since been superseded by new research, which is identified by Peter Crooks in a very useful bibliographic afterword
PUBLISHED
Keywords: Dublin; medieval; Identities in Transformation; Smart & Sustainable Planet